Costs incurred by outpatients at a university hospital in northwestern Ethiopia: a cross-sectional study - Fitsum Sebsibe Teni; Begashaw Melaku Gebresillassie; Eshetie Melese Birru; Sewunet Admasu Belachew; Yonas Getaye Tefera; Befikadu Legesse Wubishet; Bethelhem Hailu Tekleyes; Bilal Tessema Yimer (BMC, 2018)
Abstract Background Out-of-pocket expenditure constitutes high proportion of healthcare spending in low-income countries. It can affect patients' adherence to treatments leading to serious health consequences. The objective of this study was to document costs incurred by patients visiting Gondar University Referral Hospital, in Gondar, northwestern Ethiopia. Methods An institution-based cross-sectional study was conducted among 346 outpatients at the hospital from 2nd to 20th of May 2016. Data collection took place through interviews with patients coming to the outpatient pharmacy after finishing their visits at the different departments in the hospital. Data were collected on socio-demographic information, cost incurred before and during hospital visit as well as ownership of household items. Results Among the 342 interviews included in the final analysis, a median total cost of 22.25 USD was incurred by patients. This constituted spending on solutions tried before hospital visit, direct medical, nonmedical and indirect costs. Among these, direct nonmedical and indirect costs constituted a large share. Medicine, transportation and waiting time during visit were major components of direct medical, nonmedical and indirect costs respectively. Total median cost was found to be predicted by residence, marital status and payment scheme used to pay for hospital services. Conclusions Outpatients visiting the hospital incurred significant costs for illnesses/conditions associated with their visit to the hospital, the main components being nonmedical and indirect costs. Residence, marital status and payment scheme, predicted median total cost. Direct nonmedical costs and indirect costs were found to be significant components associated to the spending and loss of earning by patients and their families in their trip to and from the hospital.